Javanese Existence As Human Being in Linus Suryadi’s Pengakuan Pariyem - Amalia Rachmawati; Anita Rahmah Dewi (JELP Journal of English Language and Pedagogy, 2022)
Linus Suryadi is Indonesian writer who often use a lot of Javanese diction in his writings. One of his famous lyrical prose is Pengakuan Pariyem who tells about the life, thoughts, and spiritual belief of Javanese woman that still hold her strong culture and customs. This paper is aimed to find the existentialism aspect in the lyrical prose by using qualitative descriptive methods. It emphasizes on the habit of Javanese people according to the tradition, customs and spiritual belief that depicted in the lyrical prose to reveal the way Javanese people show their existence and looking for the meaning of life as human being. This study find out that Javanese people according to Linus Suryadi is theistic and somehow even though they have faith in the existence of God, they still mixing up between religion and ancient belief. The existentialism aspects that are portrayed in the lyrical prose are the freedom to choose, responsible of the choice, anxiety feeling, and existence precedes essence.